PENGARUH PENAMBAHAN PASIR SUNGAI PADA BATA MERAH TERHADAP KUAT TEKAN DAN PENYUSUTAN DI TALANG KERING KOTA BENGKULU - Fitri Herlina; Elhusna Elhusna; Mukhlis Islam (Inersia: Jurnal Teknik Sipil, 2019)
This report is the result of the research of the effect of river sand addition to red brick to the shrinkage and the compressive strength of the red brick. The production ofred bricks was done in brick factory in Talang Kering Kota Bengkulu. River sand derived from Taba Penanjung. The composition of the sand used was 0%, 5%, 10%, 15%, 20%, 25%, 30% of the weight of clay with the mold size of 10,5 cm x 21cm x 5 cm. The sample used for shrinkage sample is also used for compressive strength test as many as 140 pieces.Compressive strengthtesting refers to the SNI 03-4164-1996 and use compression tool hand operated machine with a capacity of 250kN. Compressive strength testing performed after the red brick with capping is7 days old. Mortar is made with a ratio of 1: 3 using the mount sandto produce mortar with compressive strength of 3,18 MPa. The results showed thatthe brick color is dominant yelloworange with lack of smooth surface and sharp edge. Depreciation smallest volume and weight of each of the addition of 30% amounting to 34,2% and 28,87%. Depreciation largest volume and weight of each of the addition of 15% sand by 39,7% and amounted to 32,96% without sand.Most powerful press red brick on the addition of 5% sand by 1,72MPa and the smallest on the addition of 30% sand at 1,24MPa. The resulting maximum compressive strength less than 2,5MPa so it does not meet the SII-0021-978.